2004
DOI: 10.1002/ajmg.b.30077
|View full text |Cite
|
Sign up to set email alerts
|

Myelin oligodendrocyte glycoprotein (MOG) gene is associated with obsessive‐compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is a severe neuropsychiatric disorder with a strong genetic component, and may involve autoimmune processes. Support for this latter hypothesis comes from the identification of a subgroup of children, described by the term pediatric autoimmune neuropsychiatric disorder associated with streptococcal infections (PANDAS), with onset of OCD symptoms following streptococcal infections. Genes involved in immune response therefore represent possible candidate genes for OCD, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Severe depression, bipolar disorder, and other neuropsychiatric disorders have also been associated with myelination deficits (Aston et al, 2005;Bartzokis, 2005;Beasley et al, 2005;Hamidi et al, 2004;McDonald et al, 2004;Tkachev et al, 2003;Uranova et al, 2005;Uranova et al, 2004;Wang et al, 2004b;Zai et al, 2004). If, as we suggest, treatment with atypical antipsychotics can mitigate myelination deficits, then such treatment could also mitigate similar deficits in these other psychiatric conditions.…”
Section: Discussionmentioning
confidence: 73%
“…Severe depression, bipolar disorder, and other neuropsychiatric disorders have also been associated with myelination deficits (Aston et al, 2005;Bartzokis, 2005;Beasley et al, 2005;Hamidi et al, 2004;McDonald et al, 2004;Tkachev et al, 2003;Uranova et al, 2005;Uranova et al, 2004;Wang et al, 2004b;Zai et al, 2004). If, as we suggest, treatment with atypical antipsychotics can mitigate myelination deficits, then such treatment could also mitigate similar deficits in these other psychiatric conditions.…”
Section: Discussionmentioning
confidence: 73%
“…Although Song et al (2003) suggested a higher RD to be associated with demyelination, others have shown that the interpretation of changes in RD and AD needs careful consideration, due to the inherent disbalance between fiber thickness and imaging resolution (WheelerKingshott and Cercignani, 2009). Although a few genetic studies suggested myelination in the OCD pathophysiology (Zai et al, 2004;Stewart et al, 2007), we can only speculate about possible disruption of myelin integrity contributing to the white matter abnormalities in the left cingulum bundle. A similar pattern of lower FA in combination with higher RD (and normal AD values) has also been reported for autism, schizophrenia, and depression Ashtari et al, 2007;Lee et al, 2007;Michael et al, 2008;Seal et al, 2008;Whitford et al, 2010;Korgaonkar et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…The authors suggested that the potentially autoimmune demyelinating role of this molecule, as a target autoantigen, could hypothetically be as an inductor of OCD, via demyelination in the frontal lobe or in other neuroanatomical regions. 152 The complexity of this model, in which a true autoimmune mechanism would be causing OCD, as well as the lack of evidence supporting it, argues for further studies.…”
Section: Environmental Factorsmentioning
confidence: 98%
“…140 However, these early findings have not been consistently replicated, and there is now considerable controversy regarding this relationship. 150,151 Finally, one recent study 152 found an association between a variant in the myelin oligodendrocyte glycoprotein (MOG) gene, a component of the myelin sheath, and OCD. The authors suggested that the potentially autoimmune demyelinating role of this molecule, as a target autoantigen, could hypothetically be as an inductor of OCD, via demyelination in the frontal lobe or in other neuroanatomical regions.…”
Section: Environmental Factorsmentioning
confidence: 99%